2011
DOI: 10.1158/1078-0432.ccr-11-1707
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic and Molecular Characterization of Malignant Peripheral Nerve Sheath Tumor Identifies the IGF1R Pathway as a Primary Target for Treatment

Abstract: Purpose Malignant peripheral nerve sheath tumor (MPNST) is a rare sarcoma that lacks effective therapeutic strategies. We gain insight into the most recurrent genetically altered pathways with the purpose of scanning possible therapeutic targets. Experimental design We performed a microarray based-comparative genomic hybridization (aCGH) profiling of two cohorts of primary MPNST tissue samples including 25 patients treated at The University of Texas MD Anderson Cancer Center and 26 patients from Tianjin Canc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 47 publications
(68 reference statements)
5
63
1
Order By: Relevance
“…On the basis of the findings of our in vitro study, it is reasonable to say that a single use of Everolimus is a potential novel drug therapy for sporadic and NF1-related MPNSTs. However, further in vivo and in vitro investigations in combination with other kinase inhibitors or cytotoxic agents are encouraged because the mTOR inhibitor might show stronger antitumor activity when administered in combination (24,41,45,46). This study revealed that AKT/mTOR/S6RP activation was not only suitable as a treatment target, but also useful for prognostication.…”
Section: Discussionmentioning
confidence: 86%
“…On the basis of the findings of our in vitro study, it is reasonable to say that a single use of Everolimus is a potential novel drug therapy for sporadic and NF1-related MPNSTs. However, further in vivo and in vitro investigations in combination with other kinase inhibitors or cytotoxic agents are encouraged because the mTOR inhibitor might show stronger antitumor activity when administered in combination (24,41,45,46). This study revealed that AKT/mTOR/S6RP activation was not only suitable as a treatment target, but also useful for prognostication.…”
Section: Discussionmentioning
confidence: 86%
“…46 Therefore, IGF1R has been identified as a potential molecular target for several cancer types, including breast cancer, cervical cancer, malignant melanoma and NSCLC. 47 Moreover, the activation of IGF-1R and its downstream pathways has critical roles in the normal development of many tissues and is believed to be important for the maintenance of tissue-resident adult stem cells. 48 IGF-1R-mediated signaling is also required for embryonic stem cell self-renewal, 49 indicating an important role for IGF-1R in stem cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…As part of this effort, several laboratories have explored the possibility that aberrant growth factor signaling is a key upstream mediator of Ras activation in MPNSTs. These studies identified several growth factors and growth factor receptors that potentially contribute to neurofibroma and MPNST pathogenesis, including the epidermal growth factor (EGF) receptor, 24 neuregulin-1 (NRG1), 24 platelet-derived growth factor, 24 hepatocyte growth factor, and its c-Met receptor, 24 the insulin-like growth factor 1 receptor, 51 transforming growth factor-b1, 52 lysophosphatidic acid, 53 midkine, 52 Kit ligand and its c-Kit receptor, 24 CXCR4 and its CXCL12 ligand, 54 basic fibroblast growth factor, and vascular endothelial growth factor. 55 However, the strength of the evidence…”
Section: Genomic Abnormalities Mediating Neurofibroma-mpnst Progressionmentioning
confidence: 99%